Thermal aging behaviour of an aluminised explosive charge. (December 2015) - Jia, L.; Zhang, L. J.; Zhang, D. M.; Du, J. J.; Xin, K. D.; Luan, J. Y.; Zhou, W. J.; Wang, K. Y.; Han, F.
Abstract : The desensitised 1, 3, 5-trinitro-1, 3, 5-triazinane (RDX) and Al powder, after being coated up with ethylene vinyl acetate copolymer (EVA), were compressed into cylindrical grains of Ф20 × 30, 40 × 40 and 60 × 60 mm. After aging at 71°C for 39 days, the aging behaviour of grains were investigated by using the scanning electronic microscope, laser microscope, raman spectroscopy, industrial computerised tomography and vacuum stability test (VST). The results showed that after aging, the micro-structure of the grains remain unchanged, the grains' mass lose for 0.1%, they do not seep oil and the amount of released gas in VST changed from 0.08 to 0.04 mL g −1, their porosity increased from 8.5 to 10.1% and their density changed from 1.755 to 1.750 g cm −3 . This proves that the aging has enabled the grains to remain unchanged in mass and their physical stability remains unchanged, because the EVA coating prevented the desensitiser from flowing; and the grains' chemical stability is good; EVA has considerably reduced the degree of enlarging of grains' volume.